Biography and ornamentalism – a postmodern novel about Dostoyevsky (Leonid Tsypkin’s Summer in Baden-Baden) - Szabó, Tünde (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2017)
The paper examines how Leonid Tsypkin’s novel Summer in Baden-Baden utilises the apparatus of symbolist ornamental prose, one of the characteristic features of Russian Modernism, while it applies postmodern devices to construct the myth of Dostoyevsky as a gambler. The plot of Tsypkin’s novel, which relies on primary sources, especially Anna Dostoyevskaya’s diary, highlights the feeling of humiliation as a central component of the personality of Dostoyevsky as a character. At the same time, on the ornamental level of the text, repetitive motifs and equivalences are applied with the aim of placing emphasis on transcending the humiliation, which can be achieved through “aspiring for the summit” and a network of motifs connected with it. As a result, the motif structure of The Gambler, the most autobiographical of Dostoyevsky’s novels, becomes transcoded.